Angular Light Scattering of Gold Nanoparticles on Graphene Oxide - Hüseyin, Tepe (My University, 2016)
Lately, the study of plasmon excitations have been a rapidly growing subject. Some applications are light trapping, sensing and catalysis. The scattering characteristics of particles depends on the size of the particle and the environment. The aim of this study is to perform angular resolved measurements on gold nanoparticles imbedded in graphene oxide akes. The angular scattering intensities and peaks were measured. The e ect of changing environment on the scattering spectrum was also studied. Peak shifts were observed for changing dielectric environment. Changing the dielectric environment, from a citric bu er to graphene oxide on fused silica, led to a peak shift from 541 nm to 573 nm. The angular intensity measurements revealed possibly a di raction pattern, which changed for di erent wavelenghts. Angular scattering measurements showed the weakness of the sample preparation method. The sample was therefore modi ed, and angular scattering measurements were conducted, which showed di erent scattering peaks at di erent observation angles.
Keywords: Nanoteknik; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Nanovetenskap och nanoteknik; Nano Technology; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Nanoscience & Nanotechnology